Signatures of increasing environmental stress in bumblebee wings over the past century: Insights from museum specimens. Issue 2 (17th August 2022) - Arce, Andres N.; Cantwell‐Jones, Aoife; Tansley, Michael; Barnes, Ian; Brace, Selina; Mullin, Victoria E.; Notton, David; Ollerton, Jeff; Eatough, Emma; Rhodes, Marcus W.; Bian, Xueni; Hogan, James; et al.
Abstract: Determining when animal populations have experienced stress in the past is fundamental to understanding how risk factors drive contemporary and future species' responses to environmental change. For insects, quantifying stress and associating it with environmental factors has been challenging due to a paucity of time‐series data and because detectable population‐level responses can show varying lag effects. One solution is to leverage historic entomological specimens to detect morphological proxies of stress experienced at the time stressors emerged, allowing us to more accurately determine population responses. Here we studied specimens of four bumblebee species, an invaluable group of insect pollinators, from five museums collected across Britain over the 20th century. We calculated the degree of fluctuating asymmetry ( FA ; random deviations from bilateral symmetry) between the right and left forewings as a potential proxy of developmental stress. We: (a) investigated whether baseline FA levels vary between species, and how this compares between the first and second half of the century; (b) determined the extent of FA change over the century in the four bumblebee species, and whether this followed a linear or nonlinear trend; (c) tested which annual climatic conditions correlated with increased FA in bumblebees. Species differed in their baseline FA, with FA being higher in the two species that have recently expanded their ranges in Britain. Overall, FA significantly increased over the century but followed a nonlinear trend, with the increase starting c . 1925. We found relatively warm and wet years were associated with higher FA . Collectively our findings show that FA in bumblebees increased over the 20th century and under weather conditions that will likely increase in frequency with climate change. By plotting FA trends and quantifying the contribution of annual climate conditions on past populations, we provide an important step towards improving our understanding of how environmental factors could impact future populations of wild beneficial insects. Abstract : Determining stress events improves our understanding of the drivers of population declines, but a lack of baseline data makes this challenging. Leveraging museum specimens, the authors measured the change in bumblebee wing‐shape fluctuating asymmetry ( FA ; proxy of stress) between 1900 and 2000. FA increased over the century, with warmer, wetter conditions predicting higher FA .